Principales fungicidas químicos para el control del hongo Fusarium verticillioides, que afectan en el cultivo de maíz (Zea mays L.)” - Morán Barreiro, Jonathan Jayro (2022)
This document was developed with the purpose of searching for the main chemical fungicides for the control of the fungus Fusarium verticillioides, which affect corn cultivation. Among the conclusions, it was determined that Fusarium verticillioides is one of the main pathogens within the complex of fungi that attack corn cultivation, both globally and nationally, penetrating through the plant, especially through roots, stems and cob, producing a certain class of toxins that affect plant tissue and grains, reducing yields and production quality; chemical products, mainly fungicides, allow the control of F. verticillioides, which, using it in mixtures and in adequate doses, allows to reduce production costs and, in turn, does not cause environmental deterioration due to its indiscriminate use; The main chemical fungicides for F. verticillioides in corn crops are Captan, Quintozeno, Fludioxonil + Metalaxil-M, Difenoconazole, Carboxin + Thiram, considered the most used products for the control of this pathogen and the best chemical product that controls F. verticillioides in corn cultivation is the mixture of Fludioxonil + Metalaxil-M, which in our country is marketed as a commercial product that contains the two active ingredients Fludioxonil, which belongs to the chemical group of phenylpyrroles, a molecule active against a wide spectrum of higher fungi, Ascomycetes, Basidiomycetes and Deutoromycetes present in the seed and in the soil and Metalaxyl-M, which belongs to the chemical group of Phenylamines, a molecule active against fungi of the Oomycetes class.